1998
DOI: 10.4269/ajtmh.1998.58.470
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between intestinal parasitosis, physical growth, and psychomotor development among infants and children from rural Nicaragua.

Abstract: The correlations between malnutrition, parasitosis (especially helminth infections), and child development are complex, and studies of these interrelationships will allow health agencies to maximize screening and intervention strategies for developing countries. We examined these correlations in a cross-sectional program in Carazo State, Nicaragua. Nine hundred sixty-one children in two age strata (ages 0-24 months and ages 2-10 years) from one urban and three rural communities were screened for intestinal par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 9 publications
3
95
0
18
Order By: Relevance
“…A number of issues have significantly strengthened the link between malnutrition and parasitic helminth infections other than S. mansoni (Oberhelman et al 1998, Stephenson et al 2000, Crompton & Nesheim 2002, Muniz et al 2002. All studies support the view that parasites may negatively influence the host's nutritional status, and with it, physical growth, psychomotor and educational developments are also affected (Stephenson et al 2000).…”
Section: Discussionmentioning
confidence: 50%
“…A number of issues have significantly strengthened the link between malnutrition and parasitic helminth infections other than S. mansoni (Oberhelman et al 1998, Stephenson et al 2000, Crompton & Nesheim 2002, Muniz et al 2002. All studies support the view that parasites may negatively influence the host's nutritional status, and with it, physical growth, psychomotor and educational developments are also affected (Stephenson et al 2000).…”
Section: Discussionmentioning
confidence: 50%
“…These infections are regarded as a serious public health problem as they can cause iron-deficiency anaemia (5,6), malnutrition (7), growth retardation in children and other physical and mental health disorders (8,9). Most clinicians and health workers do not consider parasitic infections as life threating, and most of the time they go unnoticed or are misdiagnosed (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that prolonged use of HAART, particularly of protease inhibitors, has an important impact on user nutritional status. The relationship between infections caused by intestinal parasites and some nutritional indicators has been proven in numerous studies involving nutritional status, infection prevalence and intensity (14)(15)(16)(17)(18)(19)(20). Malnutrition has a serious influence on immunity aspects, including the production of cytokines and antibodies, particularly Th2 profile (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%